Comparison of Surgical Outcomes for Distal Rectus Femoris Transfer and Resection Surgeries in Children With Cerebral Palsy With Stiff Knee Gait. Issue 8 (19th September 2021) - Salazar-Torres, Jose J.; Church, Chris; Shields, Thomas; Lennon, Nancy; Shrader, M. Wade; Sees, Julieanne P.; Miller, Freeman
Abstract : Background: Children with cerebral palsy (CP) often present with a stiff knee gait pattern because of rectus femoris (RF) spasticity and/or contracture. Rectus femoris transfers (RFTs) and resections are surgical procedures aimed at reducing muscle stiffness, thereby improving knee flexion during the swing phase of gait. Previous research has consistently demonstrated objective benefits of rectus transfer using instrumented gait analysis (IGA). Rectus femoris resection (RFR), a relatively simpler procedure, shows similar improvement in knee range of motion during gait. The objective of this study was to compare surgical outcomes between rectus transfers and resections using 3-dimensional IGA. Methods: Children with spastic CP who had RFTs or resections were retrospectively matched by walking speed and preoperative knee kinematics from 3-dimensional IGA (peak and timing of peak knee flexion in swing). Secondary outcomes included knee range of motion and maximum knee extension during gait. Results: Twenty-eight children were included in both the transfer group [age 9.4±2 y; Gross Motor Function Classification System (GMFCS) I (3 children), II (15 children), III (8 children), and IV (2 children)] and the resection group [age 10.6±2.5 y; GMFCS I (1 child), II (14 children), and III (13 children)]. Both surgical groups showed statistically significant short-term postsurgical improvements in peak knee flexion during swing ( P <0.001 for the transfer group and P =0.003 for the resection group) and Duncan-Ely test ( P =0.004 for the transfer group and P <0.001 for the resection group). Further analysis by GMFCS level showed children at GMFCS levels III/IV had a greater tendency to crouch after RFT when compared with children at GMFCS levels I/II. This tendency was not observed in the RFR group. Conclusions: Both transfer and resection surgeries significantly improved gait kinematics short-term outcomes in children with spastic CP who present with stiff knee gait pattern. Further studies are required to compare long-term outcomes of both surgeries. Level of Evidence: Level III—retrospective matched-cohort study.